New Generating Function Relations for the q-Generalized Cesàro Polynomials. (24th April 2019) - Özmen, Nejla
Abstract : The main purpose of this paper is to examine a basic (orq - ) analogue of the generalized Cesàro polynomials described here. We derive a bilateralq - generating function involving basic analogue of Fox'sH - function andq - generalized Cesàro polynomials.